DECISION SUPPORT SYSTEM PENENTUAN JENIS AYAM PETELUR MENGGUNAKAN METODE AHP (ANALITYCAL HIERARCY PROCESS) - Tri Susilowati; Andri Agung Dwi Saputra (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2018)
The development of laying chicken farming in Indonesia is very rapid, especially laying chicken that produces eggs brown. Determination of good quality chicken is needed to increase consumer satisfaction of laying chicken of Indonesia. Laying chickens to be reared should have good quality for optimal results. Laying hens are chickens whose purpose is to produce eggs. This type of laying hen is has characteristics that are nervous or easily surprised, lean body shape, white ears, and eggshell berabah putih white. Another characteristic is high egg production (200 grains / head / year), efficient in ration to form eggs, and does not have the nature of incubation. Based on the value of the purpose and economic value of the type of laying hens have a slim body or small size. Lightweight scales. From several stages of calculation or consideration of the criteria that have been determined in the research using the method Analitycal Hierarchy process then obtained the highest results on Chicken Race Chocolate alternative (Hybrid Chicken) as the type of laying hens considered suitable for cultivation.